2023
DOI: 10.1093/eurjpc/zwad029
|View full text |Cite
|
Sign up to set email alerts
|

HDL cholesterol and clinical outcomes in diabetes mellitus

Abstract: Lay Summary The aim of this study is to clarify whether fasting plasma glucose modifies the U-shaped association between high-density lipoprotein cholesterol and clinical outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Low levels of HDL are not only indicative of poor metabolic status but also a component of metabolic syndrome (3). In previous studies, HDL levels were low in diabetics (27,28). In our study, we observed that HDL levels were significantly lower in the diabetes group with poor glycemic control than in both the diabetes group with good glycemic control and the control group.…”
Section: Discussionsupporting
confidence: 61%
“…Low levels of HDL are not only indicative of poor metabolic status but also a component of metabolic syndrome (3). In previous studies, HDL levels were low in diabetics (27,28). In our study, we observed that HDL levels were significantly lower in the diabetes group with poor glycemic control than in both the diabetes group with good glycemic control and the control group.…”
Section: Discussionsupporting
confidence: 61%
“… 22 , 23 On the contrary, HDL-C in blood lipids plays a protective role. 24 A cross-sectional study involving more than 8000 diabetic patients also proved the view that HDL-C was negatively correlated with insulin resistance steady-state model (HOMA-IR). 25 The reason is that HDL-C mainly plays the role of reversing cholesterol, transporting cholesterol from peripheral tissues, including blood vessel walls, to the liver for metabolism, promoting cholesterol clearance, and maintaining lipid balance in the body.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies have identified a tight association between high levels of Non-HDL-C and low levels of HDL-C with the increased likelihood of developing T2DM [ 28 , 29 ]. In a sweeping analysis involving more than three million individuals, a U-shaped relationship between HDL-C levels and clinical outcomes in T2DM patients was observed [ 30 ]. It is particularly noted that an increment in HDL-C levels below 60 mg/dl is associated with a decreased risk of T2DM and its complications [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a sweeping analysis involving more than three million individuals, a U-shaped relationship between HDL-C levels and clinical outcomes in T2DM patients was observed [ 30 ]. It is particularly noted that an increment in HDL-C levels below 60 mg/dl is associated with a decreased risk of T2DM and its complications [ 30 ]. Furthermore, IR, which is associated with abnormal lipid values, emerges as a critical factor influencing the likelihood of T2DM development [ 31 ].…”
Section: Discussionmentioning
confidence: 99%